2019
DOI: 10.1027/1015-5759/a000405
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Dyadic Adjustment Scale

Abstract: Abstract. The Dyadic Adjustment Scale (DAS) is one of the most widely used instruments for measuring relationship quality. Considering the discrepancies across studies regarding the relationship of the underlying constructs of the DAS, the aim of the present study was to examine the factor structure of the scale by applying bifactor models using confirmatory factor analytic (CFA) and exploratory structural equation modeling (ESEM) approaches. The sample consisted of 483 couples recruited in Hungary. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…DAS is a relatively old instrument focused more on agreement than on satisfaction and could not fully capture the more positive aspects of relationships (Graham, Liu & Jeziorski, 2006). A recent study examining the DAS factor structure found acceptable reliability for the DAS consensus and cohesion subscales, but poor reliability for the satisfaction and affectional expression factors, suggesting that the interpretation of DAS scores to assess these constructs should be made with caution (Vajda, Thege & R ozsa, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…DAS is a relatively old instrument focused more on agreement than on satisfaction and could not fully capture the more positive aspects of relationships (Graham, Liu & Jeziorski, 2006). A recent study examining the DAS factor structure found acceptable reliability for the DAS consensus and cohesion subscales, but poor reliability for the satisfaction and affectional expression factors, suggesting that the interpretation of DAS scores to assess these constructs should be made with caution (Vajda, Thege & R ozsa, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results have also a variety of limitations: Firstly, it turned out that the chosen SO-subscale measures the direct attachment to the opposite person only to a certain extent even when manipulated, especially if they were unknown to each other prior to the experiment. Therefore, further studies with the IU should recruit couples, which know each other for a longer time and should use a more reliable tool as external criterion such as the dyadic relationship scale [17]. Secondly, our approach has so far only been used for the available vertical of the drawing area.…”
Section: Discussionmentioning
confidence: 99%
“…Die international etablierte Originalversion Dyadic Adjustment Scale erfasst mit 32 Items das Konstrukt der Partnerschaftsqualität mehrdimensional, wobei die ursprünglich vorgeschlagene Faktorenstruktur mit den vier Dimensionen Konsens, Zufriedenheit, Ko häsion und Gefühlsausdruck [6] zwar gelegentlich repliziert werden konnte, aber auch andere Faktorenlösungen gefunden wurden [24,25]. Obwohl die vier Items der hier untersuchten ultrakurzen DAS-4 nicht primär nach theoretischen Aspekten, sondern mittels IRT-Analysen ausgewählt wurden, werden sie traditionell dem Faktor Zufriedenheit zugeordnet, der für das übergeordnete Konstrukt der Paarqualität von essentieller Bedeutung ist [8].…”
Section: Diskussionunclassified